Clinical, hormonal and pathomorphological markers of somatotroph pituitary neuroendocrine tumors predicting the treatment outcome in acromegaly - Tomasik, Agnieszka; Stelmachowska-Banaś, Maria; Maksymowicz, Maria; Czajka-Oraniec, Izabella; Raczkiewicz, Dorota; Zieliński, Grzegorz; Kunicki, Jacek; Zgliczyński, Wojciech (Frontiers in Endocrinology, 2022)
Background Transsphenoidal adenomectomy (TSS) of somatotroph pituitary neuroendocrine tumor (PitNET) is the first-line treatment of acromegaly. Pharmacological treatment is recommended if surgery is contraindicated or did not lead to disease remission. The choice of treatment best fitting each patientshould be based on thorough investigation of patients' characteristics. The current analysis attempts to create a tool for personalized treatment planning. Aim: This study aimed to assess whether clinical, biochemical, imaging and pathological characteristics can predict surgical remission and response to first-generation somatostatin receptor ligands (SRLs) and pasireotide-LAR in acromegaly. Patients and methods: A retrospective study of 153 acromegaly patients, treated in the Department of Endocrinology in Bielanski Hospital in Warsaw, Poland was performed. Data on demographics, hormonal and imaging results, pathological evaluation, and treatment outcome was extracted from the Polish Acromegaly Registry collecting information from 11 endocrinology centers in Poland and analyzed. Results: Patients with surgical remission had lower GH and IGF-1 concentrations at diagnosis (median GH 5.5µg/L [IQR: 3.1-16.0] vs. 19.9µg/L [IQR: 9.8-42.4], p=<0.001 and mean IGF-13.1xULN±SD=1.2 vs. 3.7xULN±SD=1.2, p=0.007, respectively) and smaller tumors (median 12.5mm [IQR:9-19] vs. 23mm [IQR:18-30], p<0.001). These tumors were more often densely granulated (DG) (73.2% vs. 40.0%, p=0.001) with positive staining for alpha-subunit (α-SU) (58.3% vs. 35.5%, p=0.021) and lower Ki-67 index (p=0.002). Patients responding well to SRLs were more often male (55.6% vs. 44.4%, p=0.026), presented lower GH concentration (median GH 17.2µg/L [IQR: 6.2-29.0] vs. 23.8µg/L [IQR: 11.2-49.5], p=0.048) and had more often DG tumors (63.0% vs. 14.3%, p<0.001). No significant differences between good and poor-response to pasireotide-LAR groups were found. In multivariate logistic regression analysis fasting GH concentration<8.63µg/L, maximal tumor diameter<15.5mm, normoprolactinemia and DG tumor turned out to be independent predictors of surgical remission (OR=0.92,p=0.026; OR=0.87, p=0.069, OR=3.86, p=0.096 and OR=3.05,p=0.181, respectively). Fasting GH concentration <36.6µg/L and DG tumor turned out to be independent predictors of good response to first-generation SRLs (OR=0.96,p=0.06 and OR=10.68,p=0.002, respectively). Conclusions: Younger age at diagnosis, male sex, lower GH, IGF-1 and PRL concentrations, smaller tumor size at diagnosis as well as positive α-SU staining, lower Ki-67 index and DG tumors predicted better treatment outcome in acromegaly patients.